Uncertainty of the wheel-rail angle of attack measurements using laser based wayside system - Milković Dragan D.; Simić Goran Ž.; Tanasković Jovan D.; Lučanin Vojkan J.; Radulović Saša Z. (FME Transactions, 2017)
The angle of attack is an important wheel-rail contact parameter. Together with wheel-rail contact forces it serves for estimation of the rail vehicle curving performances. This paper analyses measurement uncertainty of the specially designed laser system for measurements of the wheel-rail angle of attack, with emphasis on the importance of the theoretical approach for selection of the appropriate measuring principle and for identifying all influential factors. The influence of the correct installation of the system on results is also considered. In order to evaluate quality of the analysis, some measurement results are presented and compared with the results of multibody system (MBS) simulation using specialized computer package VAMPIRE Pro.